Fertility cryopreservation - Chian, Ri-Cheng; Quinn, Patrick 1946- (Cambridge University Press, 2010)
Protecting the reproductive potential of young patients undergoing cancer therapy is increasingly important. With modern treatment protocols, 80% of patients can be expected to survive. It has been estimated that up to one in 250 young adults will be a survivor of childhood cancer in the future; infertility, however, may be a consequence. As a wide range of fertility preservation methods are increasingly offered by clinicians, this systematic and comprehensive textbook dealing with the cryobiology, technology and clinical approach to this therapy will be essential reading to infertility specialists, embryologists, oncologists, cryobiologists, ObGyns, andrologists, and urologists with an interest in fertility preservation. Fertility Cryopreservation reviews all the techniques of this increasingly important field within reproductive medicine. It covers the basic principles of pertinent cryobiology, and contains major sections on the different therapies available, written by international specialists combining experience from both academic centers and commercial industries